Searching for Common Threads: Understanding the Multiple Effects of Diversity in Organizational Groups - Milliken, Frances J.; Martins, Luis L. (Academy of Management Review, 1996)
Frances J. Milliken, Luis L. Martins, Searching for Common Threads: Understanding the Multiple Effects of Diversity in Organizational Groups, The Academy of Management Review, Vol. 21, No. 2 (Apr., 1996), pp. 402-433